2017
DOI: 10.1038/ncomms13980
|View full text |Cite|
|
Sign up to set email alerts
|

DNA damage response inhibition at dysfunctional telomeres by modulation of telomeric DNA damage response RNAs

Abstract: The DNA damage response (DDR) is a set of cellular events that follows the generation of DNA damage. Recently, site-specific small non-coding RNAs, also termed DNA damage response RNAs (DDRNAs), have been shown to play a role in DDR signalling and DNA repair. Dysfunctional telomeres activate DDR in ageing, cancer and an increasing number of identified pathological conditions. Here we show that, in mammals, telomere dysfunction induces the transcription of telomeric DDRNAs (tDDRNAs) and their longer precursors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(121 citation statements)
references
References 45 publications
10
110
1
Order By: Relevance
“…Indeed, DROSHA knockdown strongly impairs NHEJ repair efficiency to an extent similar to the inactivation of KU80, a central player in this repair pathway. Consistent with this result, a recent report from our group demonstrated that DROSHA inactivation results in a decrease in telomeric fusions, a process that relies on NHEJ (Rossiello et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Indeed, DROSHA knockdown strongly impairs NHEJ repair efficiency to an extent similar to the inactivation of KU80, a central player in this repair pathway. Consistent with this result, a recent report from our group demonstrated that DROSHA inactivation results in a decrease in telomeric fusions, a process that relies on NHEJ (Rossiello et al, 2017).…”
Section: Discussionsupporting
confidence: 77%
“…Importantly, dilncRNA generation provides the RNA precursor for DDRNA generation upon DROSHA and DICER processing and, concomitantly, a sequence specific recruiting element for mature DDRNA together with DDR protein factors to which they associate . Similarly, we have shown that DDRNAs with telomeric sequences activate DDR at unprotected telomeres, which resemble DSBs (Rossiello et al, 2017). Interestingly, DROSHA inactivation by siRNA prevents telomere fusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of telomere length are hampered by noise and wide longitudinal variations that cannot be explained by health events and at this stage are not useful for measuring biological age (Arai et al, 2015;Jodczyk, Fergusson, Horwood, Pearson, & Kennedy, 2014;Tomaska & Nosek, 2009). New methods are being developed, some of which are focused on detecting the DNA damage response (a typical marker of critical telomere shortening) may yield better results (Choi, Kim, Kim, Kemp, & Sancar, 2015;Hewitt et al, 2012;Rossiello et al, 2017). Senescence has been studied successfully in T lymphocytes, skin, and intramuscular fat, and high-throughput methods will be available soon (Evangelou et al, 2016;Lozano-Torres et al, 2017).…”
Section: Connec Ting the B I Ology Of Ag Ing With Ag E-a Sso Ciatedmentioning
confidence: 99%
“…Telomeric small RNAs have also been detected in mouse embryonic stem cells (Cao et al, 2009). Telomere dysfunction can induce production of telomeric siRNAs with perfect homology to the vertebrate telomere repeat sequence (TTAGGC)n, which are created by dsRNAs that arise from sites of DNA damage and are processsed by Dicer into siRNAs that promote the DNA damage response (Rossiello et al, 2017). However, the origin of small RNAs with homology to telomeres that are present under standard growth conditions of wildtype metazoan cells is not well understood.…”
Section: Introductionmentioning
confidence: 99%